MAPPING THE SPEED OF CAPITAL STRUCTURE ADJUSTMENT:A SYSTEMATIC AND STRUCTURAL SYNTHESIS OF FOUR DECADES OF EVIDENCE (Contemporary Journal of Social Science Review, 2025)
This paper seeks to provide a systematic literature review on the speed of adjustment (SOA) of capital structure between 1984 and 2025, providing the major themes and recommending the potential areas that can be used in future investigation. Unlike the general reviews of capital structure, the study is concerned with the sub-area of speed of adjustments and its changing dynamics. The review uses systematic method to select and analyze the related studies and apply bibliometric tools and systems thinking approach to reviewing, identifying current trends of research and new research directions. The results indicate that there has been a drastic evolution in the concept of SOA, especially in terms of dynamic models that analyze how the adjustment costs, economic environments, corporate governance, and other factors affect the financial policies of firms. This study provides novel insights to understand the intellectual structure of the field by utilizing the co-citation analysis, keyword network, and clusters of themes, and highlights the gaps in the research and introduces the future research directions The study is done through published works present in the SCOPUS database, while studies that were not considered during the study may or may not affect the conclusions. The review is also using an innovative "systems engineering thinking approach" to establishing literature gaps, which makes a multidisciplinary contribution to the research work on the topic of capital structure adjustment.